2004
DOI: 10.1186/1477-7525-2-36
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: BackgroundThe Self-Perception and Relationships Tool (S-PRT) is intended to be a clinically responsive and holistic assessment of patients' experience of illness and subjective Health Related Quality of Life (HRQL).MethodsA diversity of patients were involved in two phases of this study. Patient samples included individuals involved with renal, cardiology, psychiatric, cancer, chronic pelvic pain, and sleep services. In Phase I, five patient focus groups generated 128 perceptual rating scales. These scales des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 43 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…(3) Uremic symptoms questionnaire: This questionnaire is derived from the "Symptom Assessment Instrument" by Weisbord et al [140], which was created and validated in US veterans with stage 5 CKD. (4) Self-Perception and Relationship Questionnaire: This item will assess the psychosocial-spiritual well-being using the 28-item scale [141]. (5) Food Frequency Questionnaire (FFQ) [142]: this questionnaire has been developed by Kalantar-Zadeh et al using the Block FFQ from UC Berkeley, and can be used semi-annually to annually (see Table 5).…”
Section: Suggested Self-administered Questionnairesmentioning
confidence: 99%
“…(3) Uremic symptoms questionnaire: This questionnaire is derived from the "Symptom Assessment Instrument" by Weisbord et al [140], which was created and validated in US veterans with stage 5 CKD. (4) Self-Perception and Relationship Questionnaire: This item will assess the psychosocial-spiritual well-being using the 28-item scale [141]. (5) Food Frequency Questionnaire (FFQ) [142]: this questionnaire has been developed by Kalantar-Zadeh et al using the Block FFQ from UC Berkeley, and can be used semi-annually to annually (see Table 5).…”
Section: Suggested Self-administered Questionnairesmentioning
confidence: 99%
“…Ore and Foli [28] recently published a concept analysis on reintegration post-cancer treatment that demonstrated the dynamic and evolving nature of this outcome, which involves a reorganization of roles and personal abilities to create a new normal and post-treatment identity. The authors provide some suggested tools to help assess this concept such as symptom scales as well as the Self-Perception and Relationships Tool [29] and the Reintegration to Normal Living Index [30]. The latter is a provider-reported tool used mainly in rehabilitation settings to assess the degree to which individuals who have experienced traumatic or incapacitating illness achieve reintegration into normal activities.…”
Section: Discussionmentioning
confidence: 99%
“…and "Are these changes something that you act upon?" The Self-Perception and Relationships Tool (Atkinson, Wishart, Wasil, & Robinson, 2004) is a holistic assessment used to measure self-perceptions throughout the health care process. Such an assessment could prove valuable across many cancer populations (Atkinson et al, 2004).…”
Section: Empirical Referentsmentioning
confidence: 99%
“…The Self-Perception and Relationships Tool (Atkinson, Wishart, Wasil, & Robinson, 2004) is a holistic assessment used to measure self-perceptions throughout the health care process. Such an assessment could prove valuable across many cancer populations (Atkinson et al, 2004). Quickly identifying survivors who are in the process of reorganizing or reevaluating aspects of their lives can assist nurses with early supportive interventions and drive more effective health care strategies.…”
Section: Empirical Referentsmentioning
confidence: 99%